Faktor Penyebab Penurunan Popularitas Wisata Air Terjun Curug Embun - Tamara Dwi Putri; Farida R Wargadalem; M Taofik Kurohman (Institut Citra Internasional, 2025)
Curug Embun is a well-known natural tourist destination in Pagaralam City due to its pristine natural beauty and towering waterfall. However, in recent years, this destination has experienced a significant decline in visitors. This study aims to identify the factors causing the decline in visitor interest and formulate a sustainable development strategy to regain its popularity. The study was conducted using a qualitative approach through observation, interviews, documentation, and literature review. The results indicate that factors such as minimal supporting facilities, inadequate access, lack of promotion, limited government involvement, and weather influences are the main causes of the decline in tourist visits. This study concludes that the management of the Curug Embun tourist destination needs to be improved through facility improvements, digital promotion, and collaboration between the government, managers, and the local community so that this tourist attraction can regain its competitiveness with other destinations.